2022
DOI: 10.1177/09589287221080700
|View full text |Cite
|
Sign up to set email alerts
|

Public policies supporting families with children across welfare regimes: An empirical assessment of six European countries

Abstract: Public policies supporting families with children differ among countries but with the same goal of improving the well-being of children. Using a microsimulation model, this article assesses the cash support which families receive for their children in Croatia, Greece, Germany, the Slovak Republic, Sweden and the United Kingdom. The impact of policies across the income distribution on different family sizes, child-rearing cost compensation and child poverty is estimated. A method for the calculation of child-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…To estimate the generosity of financial support for parents over the course of childhood and across birth orders, we adopt the method of measuring child‐contingent payments (CCP), in line with the family policy literature (Corak et al, 2005; Figari et al, 2011; Pezer, 2022). This method aggregates all forms of financial support for parents issued at specific points in time and for specific model households, including both allowance‐based and tax‐based provisions, but excluding parental leave.…”
Section: Methods and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…To estimate the generosity of financial support for parents over the course of childhood and across birth orders, we adopt the method of measuring child‐contingent payments (CCP), in line with the family policy literature (Corak et al, 2005; Figari et al, 2011; Pezer, 2022). This method aggregates all forms of financial support for parents issued at specific points in time and for specific model households, including both allowance‐based and tax‐based provisions, but excluding parental leave.…”
Section: Methods and Datamentioning
confidence: 99%
“…This tendency is attributed to shifting consumption needs over the course of childhood, leading to larger expenditure at higher child ages, mostly in domains such as extracurricular activities and entertainment. In terms of parity, it has been shown that each additional child in a household tends to cost less than the preceding child (Corak et al, 2005; Pezer, 2022). This estimation is attributed to the economies of scale that are created between birth orders in expenditure domains such as food, clothing, housing and babysitting, where siblings often enjoy resource‐sharing opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…The main object of our analysis is households with children, with particular emphasis on the cash and in-kind transfers parents receive on account of children in their household. Children are defined as below 18 years of age but we also include young dependent adults, as in Pezer (2022). Young dependent adults are economically dependent adults up to 25 years of age (students, unemployed, disabled and similar).…”
Section: Methods and Assumptionsmentioning
confidence: 99%
“…Nguyen and Rubil (2021) conclude that, based on 2018 data, the fiscal system in Croatia reduces inequalities but increases poverty: only direct transfers (disability pensions and benefits, child benefits and guaranteed minimum benefit) reduce poverty, especially for households with three or more children. Previous comparative research on child poverty indicates that Croatian cash transfers to families are less potent than in some European countries (Pezer 2022). Pezer, Urban, and Leventi (2022) demonstrate how the inclusion of subsidies provided by local governments for kindergarten and transport greatly contributes to poverty reduction.…”
Section: Related Literaturementioning
confidence: 99%
“…They have universal social security systems and provide generous sickness, unemployment and pension benefits, regardless of prior earnings (Esping- Andersen, 1990Andersen, , 1999. Next to employment protection, social-democratic regimes make childbearing less costly for employment careers through childcare provision and parental leave (Pezer, 2022). Moreover, they support the dual-earner model, where couples equally participate in the workforce.…”
Section: Welfare Regimementioning
confidence: 99%